FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN KENDALISODO BRASSERIE PATRA JASA SEMARANG CONVENTION HOTEL - Prabowo, Heri; Hesty Puspitasari , Ratih (Universitas Ngudi Waluyo, 2020)
This study discusses the factors that influence customer satisfaction in Kendalisodo Brasserie Patra Jasa Semarang Convention Hotel. The number of samples is 105 respondents who have visited Patra Jasa Semarang more than once. The results of the analysis show satisfaction with customer satisfaction, as well as the quality of service emphasizes customer satisfaction. Likewise, the results of simultaneous trials show that facilities and service quality are related to customer satisfaction at Kendalisodo Brasserie Patra Jasa Semarang Convention Hotel.